The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.biopsych.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Backward Masking Deficit in Schizophrenia: Individual Differences in Performance and Modeling With Transcranial Magnetic Stimulation

Abstract: Background-Deficits in backward masking have been variably reported in schizophrenia patients, but individual differences in the expression of these deficits have not been explicitly investigated. In addition, increased knowledge of the visual system has opened the door for new techniques such as transcranial magnetic stimulation (TMS) to explore these deficits physiologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…40 Interestingly, when transcranial magnetic stimulation is used to interrupt processes of the occipital lobe, similar impairments in task performance are seen in schizophrenia patients and healthy control participants. 41 It may be that anomalies in gamma oscillations and lateral occipital hemodynamic response reflect the more generalized impairment in perceiving masked visual stimuli observed in schizophrenia rather than the specific early perceptual abnormalities noted in the present study and by other researchers. 8,11 Indeed, abnormal lateral occipital complex function during masking paradigms appears not to mark genetic liability for the disorder.…”
Section: Discussioncontrasting
confidence: 47%
“…40 Interestingly, when transcranial magnetic stimulation is used to interrupt processes of the occipital lobe, similar impairments in task performance are seen in schizophrenia patients and healthy control participants. 41 It may be that anomalies in gamma oscillations and lateral occipital hemodynamic response reflect the more generalized impairment in perceiving masked visual stimuli observed in schizophrenia rather than the specific early perceptual abnormalities noted in the present study and by other researchers. 8,11 Indeed, abnormal lateral occipital complex function during masking paradigms appears not to mark genetic liability for the disorder.…”
Section: Discussioncontrasting
confidence: 47%
“…This interval was chosen based on a number of previous studies that found that TMS had maximum effect on visual perception between 80 and 120 ms after stimulus onset (Amassian et al 1989;Boyer et al 2005;Corthout et al 1999;Kammer 2007;Kastner et al 1998;Luber et al 2007;Maccabee et al 1991;Miller et al 1996). In one-half of the blocks, subjects received a TMS pulse to the occipital cortex; in the other one-half of the blocks, the subjects received a pulse at the same stimulus intensity to the vertex of the head.…”
Section: Methodsmentioning
confidence: 99%
“…But this was only detected for one group, that of ''non-schizophrenic psychotics'', and all the other data in this study were of the Type-A kind. Luber et al (2007) detected a number of ripples in their masking functions (see their Figure 1). However the overall trend is that of Type-A masking.…”
Section: Type-a Masking In Schizophreniamentioning
confidence: 96%
“…Of these studies, the majority have uncovered abnormal masking on the part of the schizophrenic subjects: Braff (1989); Braff and Saccuzzo (1985); Butler et al (1996Butler et al ( , 2002, this latter study found abnormalities both under Type-A and Type-B masking, see below); Cadenhead et al (1997); Goghari and Sponheim (2008); Granholm and Verney (2004); Green et al (1994aGreen et al ( , 1994bGreen et al ( , 2003a in the case of target location and target identification with a high energy mask, 2003b); Harvey et al (1990); Keri et al (2000Keri et al ( , 2001; Knight et al (1985); Koelkebeck et al (2005); Rund (1993); Rund et al (1993); Saccuzzo et al (1974Saccuzzo et al ( , 1996; Saccuzzo and Michael (1984); Saccuzzo and Schubert (1981); Schechter et al (2003); Schü tze et al (2007); Slaghuis (2004); Slaghuis and Bakker (1995, mainly in the case of the subjects with negative-symptom schizophrenia); Slaghuis and Curran (1999); Suslow and Arolt (1997); Weiner et al (1990);and Wynn et al (2005) all found some degree of abnormal masking on the part of the schizophrenic subjects in the case of Type-A masking. Luber et al (2007) divided their schizophrenic subjects into ''good performers'' and ''unresponsive subjects'', and reported substantially abnormal masking in the latter group. Also, Braff (1981) identified deficits in schizophrenic individuals relative to depressed subjects, Braff and Saccuzzo (1981) detected abnormal masking in paranoid schizophrenic patients relative to depressed patients, …”
Section: Type-amentioning
confidence: 98%
See 1 more Smart Citation